PFKFB3 deprivation attenuates the cisplatin resistance via blocking its autophagic elimination in colorectal cancer cells - Li, Qianqian; Ma, Jianxing; Zhang, Yaqin; Sun, Fengyao; Li, Wen; Shen, Wenzhi; Ai, Zhiying; Li, Changli; Wang, Shanshan; Wei, Xiaonan; Yan, Siyuan (Frontiers in Pharmacology, 2024)
Introduction 6-Phosphofructo-2-kinase/fructose-2,6-bisphosphatase isoform 3 (PFKFB3) is highly expressed in several cancers and plays important roles during the whole pathological process of cancer. It is also involved in chemoresistance, while the intrinsic mechanism needs to be further revealed. Methods The different responses to cisplatin (DDP) between wild type (WT) and DDP-resistant (DDR) colorectal cancer (CRC) cells were analyzed by several assays. Coumarin conjugated DDP (CP-DDP) was utilized to trace the distribution of DDP. Pharmacological and genetic methods were used to deprive autophagy and PFKFB3, and the effects were investigated. The mouse xenograft model was performed to confirm the effect of the PFKFB3 inhibitor on reversing DDP resistance. Results DDR cells showed a lower capacity for apoptosis upon DDP treatment, but exhibited higher levels of autophagy and PFKFB3. CP-DDP partly co-localized with LC3, and its content lessened faster in DDR cells. Deprivation of both autophagy and PFKFB3 attenuated CP-DDP elimination, and reversed the DDP resistance. Moreover, PFKFB3 inhibition reduced DDP-induced autophagy. PFKFB3 inhibitor in combination with DDP led to a remarkable reduction in tumor growth in vivo. Discussions Inhibition of PFKFB3 reduced the autophagy induced by DDP, and therefore extended the retention time of CP-DDP. Meanwhile, PFKFB3 deprivation reversed the DDP resistance and made it a potent therapeutic target for CRC.